Beauty and skincare e-commerce mobile application with advanced searching module using image processing - Tan, Yee Shin (2020)
Beauty and skincare E-Commerce Mobile Application with Advanced Searching Module using Image Processing is designed to brings great convenience to both sellers and buyers. As ecommerce is growing much faster than retail, many people opt for online shopping and some of the young generation started to set up an e-commerce business. This project is motivated to make contribution to the consumers by providing them a convenient way to shop online with simple steps, capable of for easy browsing, online tracking, 24/7 online shopping and simple payment method. In addition, the purpose of this project is to motivate both sellers and buyers to use this mobile application for purchasing their beauty and skincare products. This project is to be developed and managed with popular system development methodology – Agile methodology. This methodology support incremental and iterative development in a consistent and disciplined way to execute the task. In agile methodology, it is mainly focus on incrementation and division of tasks into several time boxes. The proposed project aimed to be developed with current popular open source technologies. Android Studio is selected as the mobile app development tool which is easy to use and accurate programming. With Cloud Test Lab Integration, mobile app can be built for one and test on multiple android devices then further check about the compatibility and performance of an app using Android Studio. The expected implementation of mobile app selling beauty and skincare products is allow users to purchase beauty and skincare products without travelling, quick searching items by keywords and quick recognizing products by images. Moreover, there are some features such as “remember me”, “forget password”, live chat and chatbots powered software for realtime communication that developed to enhanced the user experience.